Landscape and landscape painting in revolutionary France - Adams, Steven, 1955- author.
1 online resource.
Keywords: "The French Revolution had a marked impact on the ways in which citizens saw the newly-liberated spaces in which they now lived. Painting, gardening, cinematic displays of landscape, travel guides, public festivals, tales of space flight and devil-abduction each shaped citizens' understanding of space. Through an exploration of landscape painting over some forty years, Steven Adams examines the work of artists, critics and contemporary observers who have largely escaped art historical attention to show the importance of landscape as a means of crystallising national identity in a period of unprecedented political and social change"--